АНАЛИЗ ВЗАИМОСВЯЗАННЫХ ЗАРЯДНО-РАЗРЯДНЫХ ПРОЦЕССОВ КОНДЕНСАТОРА В ЦЕПЯХ С ПОЛОЖИТЕЛЬНОЙ ОБРАТНОЙ СВЯЗЬЮ ПО НАПРЯЖЕНИЮ - Супруновская, Н.И. (Інститут електродинаміки НАН України, Київ, 2017)
The paper analyzes the interrelated cyclically repeated charge-discharge processes in the circuits of a reservoir capacitor in electric discharge installations with positive voltage feedback and a load whose resistance can vary randomly. Control of the amount of positive voltage feedback is characterized by coupling coefficient, which determine the relation of residual voltage of the capacitor discharge with the initial voltage of its subsequent charge. It is substantiated that the output voltage of electric discharge installations with positive feedback is limited in magnitude (due to energy losses in their circuits). In this case, it is possible to purposefully limit the excessive (as compared to permissible) increase in the capacitor charge voltage using an adjustable coupling coefficient 0 <k ≤ 1, which can be changed manually or automatically. References 15, figures 2, table 1.